1982
DOI: 10.2136/sssaj1982.03615995004600050025x
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term Effects of Manure on Soil Nitrogen, Phosphorus, Potassium, Sodium, Organic Matter, and Water Infiltration Rate

Abstract: High rates of manure were added to field plots of a Holtville silty clay (Typic Torrifluvents) soil in an irrigated desert region, and their effects on the soils' chemical and physical properties were measured for 9 years.Manure applications resulted in large losses of nitrogen (N), increased potassium (K) levels, increased phosphorus (P) availability, increased water intake rates during the growing season, and an N mineralization rate of about 5% after the first year. At high rates of manure application only … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
34
0
4

Year Published

1986
1986
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 69 publications
(47 citation statements)
references
References 0 publications
6
34
0
4
Order By: Relevance
“…Analysis of data revealed that soil organic matter content was significantly affected by sulphur applied with compost as presented in were also obtained by [73]. Combination of organic fertilizer suggestively increased organic matter [35] and [74].…”
Section: Soil Organic Matter Contentmentioning
confidence: 82%
“…Analysis of data revealed that soil organic matter content was significantly affected by sulphur applied with compost as presented in were also obtained by [73]. Combination of organic fertilizer suggestively increased organic matter [35] and [74].…”
Section: Soil Organic Matter Contentmentioning
confidence: 82%
“…Mudanças nos teores de P, em profundidade, têm sido associadas ao uso de esterco por longos períodos ou em doses elevadas (Culley et al, 1981;Meek et al, 1982;Sharpley et al, 1984;Sutton et al, 1986;Chang et al, 1991;Eghball et al, 1996), indicando a importância do montante de P adicionado na movimentação. Meek et al (1982) Os teores de K no solo, após seis anos, ficaram muito abaixo do observado no início do experimento, e o teor deste mostrou-se indiferente às doses de adubação mineral aplicadas, em todas as profundidades avaliadas (Quadro 4). Na maioria dos trabalhos realizados na região Sul do Brasil, têm-se encontrado baixas respostas das culturas à adubação potássica (Sherer, 1998;Brunetto et al, 2005).…”
Section: Resultsunclassified
“…Assim, o uso de elevadas doses pode aumentar K no solo em profundidade (Vitosh et al, 1973;Meek et al, 1982;Sutton et al, 1986) em área de produção de grãos, mas não garante o mesmo efeito sob produção de silagem, sobretudo quando o solo apresenta elevada capacidade de fixação de K (Vitosh et al, 1973;Culley et al, 1981).…”
Section: Resultsunclassified
See 2 more Smart Citations